Effectiveness of ChatGPT in Identifying and Accurately Guiding Patients in Rhinoplasty Complications - Soto-Galindo, Germán A.; Capelleras, Marta; Cruellas, Marc; Apaydin, Fazil (Facial Plastic Surgery, 2023)
Postoperative complications in rhinoplasty require prompt intervention for optimal outcomes. ChatGPT, an artificial intelligence (AI) tool, offers potential for assisting in postoperative care.This study aims to assess ChatGPT's effectiveness in providing guidance for various rhinoplasty complications.Different complication scenarios were input into ChatGPT. Responses were categorized into “Contact Surgeon” or “Follow Postoperative Instructions.”ChatGPT consistently advised immediate surgeon contact for infection. For other complications, it recommended monitoring and adhering to instructions while suggesting surgeon contact if concerns persisted.ChatGPT shows promise in aiding patients' postoperative care by accurately identifying cases necessitating communication with surgeons or emergency care. This research underscores AI's potential in enhancing patient-centered care and contributes to the evolving landscape of health care practices.
Keywords: artificial intelligence; rhinoplasty; complication; ChatGPT